SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI MENGGUNAKAN METODE GRAPHIC RATING SCALES DAN 360 DERAJAT - Sulistyawan, Fariz; Wurijanto, Tutut; Subiyantoro, Yohanes Y. (Jurnal JSIKA, 2013)
PT. ALP Petro Industry is a lubricant factory under the supervision of Agip Petroli SPA Italy, PT. ALP Petro Industry is a performance appraisal has been done it still takes a long time, due to perform manual calculations that take a long time. assessment is still one-way, this leads to high performance subjectivity, because there are several criteria that no supporting data such as assessment criteria for personal skills, so that assessment is based on personal opinion of a valuer. To support the company´s business is it necessary to have a performance appraisal system of employees to be able to overcome the obstacles that occur, with the aim of assisting the employer in conducting an objective assessment of performance against an employee based on established criteria. Where the method is considered the company´s condition at this time is to use a method of Graphic rating scales and 360 degrees.   Keywords : Employees, Performance Appraisal, Graphic Rating Scales, 360 degrees